Importance of empathy among medical doctors to ensure high-quality healthcare level - Mainul Haque (Advances in Human Biology, 2019)
Patients hunt for genuine empathy from their medical doctor. Empathy is an affective mode of understanding. Empathy involves being enthused by another's experiences. However, a leading group medical doctors defines empathy as 'the act of correctly acknowledging the emotional state of another without experiencing that state oneself'. Beyond the field of medicine, empathy is an approach to understanding that precisely involves emotional resonance. However, mentioned definition of empathy primarily gives emphasis to an intellectual component rather than emotional form. Medical educationist and medical professional bodies increasingly recognise the importance of empathy because there are a lot report published regarding poor empathy level among medical doctors. This article will try to discuss emphasising on educational intervention which improves empathy level and its influence on healthcare.